ELECTRIC MACHINE WITH AXIAL MAGNETIC FLUX, PERMANENT MAGNETS AND MULTILAYERED PRINTING WINDINGS - В.В. Гребеніков; Р.В. Гамалія; А.Н. Соколовський (Технічна електродинаміка, 2020)
The use of printed windings in electric machines with permanent magnets and axial magnetic flux allows to reduce their axial size and significantly to increase the current density in the windings. Experimental studies of printed windings for heating confirmed that at a current density of J = 22 A / mm2, the steady-state temperature of the printed windings does not exceed 80 °C. For given dimensions of an electric machine with axial magnetic flux, permanent magnets and multilayer printed windings (outer diameter of the stator, axial length of the stator), numerical studies were carried out and the optimal thickness of the permanent magnets was determined at which the maximum value of the electromagnetic torque is reached. Also, as a result of numerical studies, it was found that the presence of teeth on the stator allows you to increase the electromagnetic torque of the electric machine by about 25% compared with the version of the magnetic system without teeth on the stator. A prototype of an electric machine with multilayer printed windings was made and the dependences of voltage and power in the generator mode were determined when connecting the windings through the rectifier diode bridge to the active load. The computational model of the generator adequately describes the physical model. The difference discrepancy between the calculated and experimental values ​​does not exceed. It is shown that the average difference discrepancy between the experimental and calculated values ​​does not exceed ε = 5.5%. The characteristics of the studied generators are calculated in the Simcenter MagNet and Simcenter MotorSolve software packages. References 10, figures 7, table 1.